2019
DOI: 10.3389/fninf.2019.00022
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Magnetic Stimulation to the Middle Frontal Gyrus During Attention Modes Induced Dynamic Module Reconfiguration in Brain Networks

Abstract: The interaction between dorsal and ventral attention networks (VANs) is mediated by the middle frontal gyrus (MFG), which is functionally connected to both networks. However, the direct role of the MFG in selective and sustained attention remains controversial. In the current study, we used transcranial magnetic stimulation (TMS) and electroencephalography (EEG) to probe the connectivity dynamic changes of MFG-associated regions during different attention modes. The participants underwent visual, selective, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 40 publications
0
35
0
Order By: Relevance
“…We identified the left middle frontal gyrus (MFG; BA10) as a generator of alpha and beta oscillation during STRESS, and the right + left MFG during UP and EP, which contrasts with its absence during FLOW. TMS has revealed that the left MFG is related to selective visual attention tasks, while the right MFG is more implicated in sustained attention 69 . Functional MRI has also identified the MFG as an important node of the inhibitory control network, which comprises 25 connections involving nodes in the orbitofrontal cortex, the inferior frontal gyrus, and the limbic, occipito-parietal areas 51 .…”
Section: Discussionmentioning
confidence: 99%
“…We identified the left middle frontal gyrus (MFG; BA10) as a generator of alpha and beta oscillation during STRESS, and the right + left MFG during UP and EP, which contrasts with its absence during FLOW. TMS has revealed that the left MFG is related to selective visual attention tasks, while the right MFG is more implicated in sustained attention 69 . Functional MRI has also identified the MFG as an important node of the inhibitory control network, which comprises 25 connections involving nodes in the orbitofrontal cortex, the inferior frontal gyrus, and the limbic, occipito-parietal areas 51 .…”
Section: Discussionmentioning
confidence: 99%
“…It mainly works for integrating the afferent information from other brain regions and organizing efferent impulses timely, to ensure the overall synergy between the nervous system and psychosocial processes. It involves in a variety of higher functioning processing, including memory, abstract thinking, judgment, emotion, personality and impulsive behavior, etc (55)(56)(57)(58)(59). Hence, the enhancement of functional connections in frontal lobe with the LDPFC, such as MFG and IFG, has a strong connection with the improvement of cognitive function.…”
Section: Neural Activity and Fc Changes After Rtms Treatmentmentioning
confidence: 99%
“…Other clusters of activation in significant interactions are, among others, the middle frontal gyrus as well as the inferior frontal gyrus. These regions have also proven to be part of the WM system; the middle frontal gyrus plays a crucial role in regulating attention networks and is known to be involved in attention processing and sustained attention control ( Dumas et al, 2013 ; Song et al, 2019 ; Salminen et al, 2020 ). The CF’s incapacity of recruiting these areas the same way NCF patients do once again underlines minor cognitive involvement and inferior cerebral processing in CF.…”
Section: Discussionmentioning
confidence: 99%
“…The MFI is an instrument to assess fatigue severity and has previously been used in studies of CF in sarcoidosis (Fleischer et al, 2014;Bosse-Henck et al, 2015). For each item, a score from 1 to 5 is possible, resulting in a total score of 20-100 (Smets et al, 1995). In this study, CF was diagnosed in patients with a total score of >53 based on the 75th percentile of norm values (Schwarz et al, 2003) as primary developed by Kuhnt et al (2009) and used in several studies with cohorts of sarcoidosis patients (Hinz et al, 2011;Fleischer et al, 2014;Bosse-Henck et al, 2015).…”
Section: Assessmentsmentioning
confidence: 99%